Competition indexes for individual eucalyptus trees - Martins, Fabrina Bolzan; Soares, Carlos Pedro Boechat; Leite, Helio Garcia; de Souza, Agostinho Lopes; Castro, Renato Vinícius Oliveira (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to evaluate five distance‑independent competition indexes, in individual trees of an eucalyptus commercial plantation, and to verify the possibility of fitting a single equation for growth and height, as well as the probability of mortality for three yield classes. Data from 30 permanent plots of unthinned clonal hybrids of a Eucalyptus grandis x Eucalyptus urophylla forest, were analyzed. The competition indexes were evaluated through the simple correlation coefficient and the partial‑F test, together with an identity test to verify if a single equation could be adjusted for the three yield classes. The basal area index performed better than other competition indexes. Contrarily to what was found for diameter and height, it was possible to adjust a single equation for the three yield classes for the probability of mortality.